2006
DOI: 10.1029/2006gl026884
|View full text |Cite
|
Sign up to set email alerts
|

Does atmospheric processing of saturated hydrocarbon surfaces by NO3 lead to volatilization?

Abstract: [1] The heterogeneous oxidation of a saturated hydrocarbon monolayer by NO 3 was studied. A flow tube reactor coupled to chemical ionization mass spectrometry was used to determine the reactive uptake coefficient of NO 3 on these surfaces, and X-ray photoelectron spectroscopy (XPS) was used to investigate surface oxidation and to determine if exposure to NO 3 leads to volatilization of the organic substrate. The uptake coefficient of NO 3 by an alkane monolayer is about (8.8 ± 2.5) Â 10 À4 , which may lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
122
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(140 citation statements)
references
References 28 publications
15
122
3
Order By: Relevance
“…The detection of these two SOA products (MW 371 and MW 387) suggests that further oxidation of m/z 232, 377, and 393 is occurring in the excess isoprene experiment and contributing to SOA growth. Studies have shown that NO 3 uptake on organic surfaces (even to saturated organic surfaces) be quite rapid (Moise et al, 2002;Knopf et al, 2006;Rudich et al, 2007). Hence, it is also possible that CIMS m/z 393 (a first-generation product according to one of the formation routes) is nonvolatile enough that it partitions into the aerosol phase and its further oxidation proceeds heterogeneously.…”
Section: Proposed Mechanisms Of Soa Formationmentioning
confidence: 99%
“…The detection of these two SOA products (MW 371 and MW 387) suggests that further oxidation of m/z 232, 377, and 393 is occurring in the excess isoprene experiment and contributing to SOA growth. Studies have shown that NO 3 uptake on organic surfaces (even to saturated organic surfaces) be quite rapid (Moise et al, 2002;Knopf et al, 2006;Rudich et al, 2007). Hence, it is also possible that CIMS m/z 393 (a first-generation product according to one of the formation routes) is nonvolatile enough that it partitions into the aerosol phase and its further oxidation proceeds heterogeneously.…”
Section: Proposed Mechanisms Of Soa Formationmentioning
confidence: 99%
“…Other trace gases, such as OH and NO 3 , are also involved in important heterogeneous reactions (e.g. Bertram et al, 2001;Molina et al, 2004;Hearn and Smith, 2006;Knopf et al, 2006;Gross and Bertram, 2008;Park et al, 2008;Gross and Bertram, 2009), but have not been shown to adhere to Langmuir adsorption kinetics with subsequent surface reactions (Langmuir-Hinshelwood type reactions) and are therefore not the subject of this study. Although we attempt to use realistic values characteristic of an urban plume scenario as input parameters, our purpose is not to make exact atmospheric predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory research has concentrated on the reaction of O 3 with condensed-phase unsaturated organic compounds, e.g., oleic acid, as a proxy for chemical aging of organic aerosol (e.g., Morris et al, 2002;Hearn and Smith, 2004;Katrib et al, 2004;Thornberry and Abbatt, 2004;Hearn and Smith, 2005;Katrib et al, 2005;Knopf et al, 2005;Ziemann, 2005). Fewer studies have been conducted to investigate the chemical aging of condensed-phase saturated organics by atmospheric radicals (e.g., Bertram et al, 2001;Moise and Rudich, 2001;Eliason et al, 2004;Molina et al, 2004;Hearn and Smith, 2006;Knopf et al, 2006;Hearn et al, 2007;Lambe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the reaction of organic surfaces with OH is highly efficient compared to reaction with other radicals such as NO 3 Knopf et al, 2006) and Cl (Moise and Rudich, 2001), with OH reactive uptake probabilities anging from 0.2 to 1 (Cooper and Abbatt, 1996;Bertram et al, 2001;Molina et al 2004). A few attempts have been made to elucidate the reaction mechanism for the heterogeneous reaction of OH with organic surfaces by observing reaction products.…”
Section: Introductionmentioning
confidence: 99%